Optimal Intertemporal Taxationon Consumption and the Term Structure of Government Debt. (IMF Working Papers; Working Paper, 1988)
This paper addresses the time-consistency problem of optimal policy when intertemporal prices are inflexible. For small, open economies facing given world interest rates, it shows that a consumption tax, rather than a tax on wage income, is time-consistent under a variety of circumstances, even including some cases where the optimal tax rate is not constant over time. This result, when it applies, restores the neutrality of the term structure of government debt, and reaffirms the tax-smoothing theory of debt determination.